Evaluation of the Efects of Untreated and Treated Sugarcane Bagasse Fibers and RHA on the Physicomechanical Characteristics of Cementitious Composites - Datchossa, Abbas Tiambo; DOKO, KOUANDETÉ VALERY; Kabay, Nihat; Olodo, E.T. Emmanuel; Omur, Tarik (My University, 2023)
The utilization of agricultural residues from mills or plants, such as sugarcane bagasse (SB) and rice husk ash (RHA), may contribute to the sustainability of civil engineering and the agriculture industry. In the present paper, the efect of SB fber treatment and RHA inclusion on the fow, physical, and mechanical properties of cement mortars was investigated. Cementitious mortar mixes were prepared using 0%, 3%, and 6% untreated, heat-treated, and NaOH-treated SB fbers, and the most appropriate treatment method was chosen accordingly. Then, RHA was incorporated as 10% replacement for cement. The test results indicated that using heat-treated SB fbers was benefcial, with improved mechanical and physical properties without compromising fuidity compared to other materials. As compared to reference mortar, the incorporation of 3% untreated, heat-treated, and NaOH-treated fbers increased the compressive strength by 9.6%, 14.1%, and 9.3%, and fexural strength by 18.8%, 23.6%, and 12.1%, respectively. In addition, the 10% RHA substitution increased the compressive strength of mortar mixes by 41.2%, whereas similar fexural strength value was obtained. The combined use of RHA and 3% heat-treated fber resulted in the highest fexural strength of 7.13 MPa, while the highest compressive strength of 38 MPa was obtained in the mixes produced with 10% RHA without SB fber. The results of this study demonstrate the viability of manufacturing SB fber-reinforced cementitious composites with competitive properties and their efective use in the construction sector, which can contribute to environmental sustainability.
Keywords: Sugarcane bagasse fber · Rice husk ash · Waste utilization · Cementitious composite